Pemanfaatan Bahan Bekas Galian Lapis Permukaan Jalan Aspal Beton Dengan Pencampuran Dingin Dan Panas - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian UGM, 2005)
ABSTRAK Performance of flexible pavement (asphalt concrete) is very influenced by condition of the surface course. If the surface course has cracks, potholes or rutting, it will reduce its performance. One effort to lift up the performance is by overlay this layer. By overlay, the highway elevation will be higher, but sometimes not desired. Hence before overlaying the surface course, the old surface course has to be excavated, so the new elevation has same as the old elevation. The excavation result named is the ex material excavation asphalt concrete. This research aimed to analyze the degree of the asphalt contain of ex material excavation asphalt concrete, aggregate gradation and then the ex material excavation were processed within 2 ways : cold mixture (adding kerosene) and hot mixture ( by heating the ex material and adding asphalt)